Estudo da deflexão em vigas de concreto armado com barras não metalicas - Góes, Wesley Sampaio (2021)
This work is based on the replacement of conventional steel bars by FRP (Fiber Reinforced Polymer) bars in reinforced concrete beams. A steel reinforced concrete beam was fabricated following the recommendations of ABNT NBR 6118:2014 and beams reinforced with FRP bars were fabricated using ACI 440.1R (ACI, 2015), for a comparative study of the deflection suffered by these structures. The first design was the beam reinforced with steel bars, being designed so that the structure is in domain 3, thus having its failure mode for the yielding of the steel bar. The beams reinforced with FRP material were dimensioned so that their failure mode occurs from the crushing of the concrete. Comparing the deflections obtained with each of the analyzed models we observed that the beam reinforced with steel bars has the smallest deflection where it was already expected, knowing that one of the factors that has great influence is the modulus of elasticity.